2017
DOI: 10.1155/2017/8765154
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Reprogramming, Genome Editing, and Alternative CRISPR Cas9 Technologies for Precise Gene Therapy of Duchenne Muscular Dystrophy

Abstract: In the past decade, the development of two innovative technologies, namely, induced pluripotent stem cells (iPSCs) and the CRISPR Cas9 system, has enabled researchers to model diseases derived from patient cells and precisely edit DNA sequences of interest, respectively. In particular, Duchenne muscular dystrophy (DMD) has been an exemplary monogenic disease model for combining these technologies to demonstrate that genome editing can correct genetic mutations in DMD patient-derived iPSCs. DMD is an X-linked g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 84 publications
0
28
0
1
Order By: Relevance
“…Cellular level gene therapies are emerging as innovative approaches for researchers to target DMD related cardiac manifestations, which are often the most devastating aspects of disease progression. These new cellular therapies offer the potential to cure DMD, including the cardiomyopathy characteristics [16][17][18][19][20][21][22][23]. Putten et al demonstrated that cardiac myocyte dystrophin levels as low as 4-15% of wild type mice can delay or even partially ameliorate the effects of cardiomyopathy in the mdx mice [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular level gene therapies are emerging as innovative approaches for researchers to target DMD related cardiac manifestations, which are often the most devastating aspects of disease progression. These new cellular therapies offer the potential to cure DMD, including the cardiomyopathy characteristics [16][17][18][19][20][21][22][23]. Putten et al demonstrated that cardiac myocyte dystrophin levels as low as 4-15% of wild type mice can delay or even partially ameliorate the effects of cardiomyopathy in the mdx mice [24].…”
Section: Introductionmentioning
confidence: 99%
“…Putten et al demonstrated that cardiac myocyte dystrophin levels as low as 4-15% of wild type mice can delay or even partially ameliorate the effects of cardiomyopathy in the mdx mice [24]. Several potential gene therapies aiming at dystrophin restoration such as exon skipping, gene editing via viral vectors, and gene slicing CRISPR system delivered by adeno-associated viruses have been described in the literature, but their efficacy in dystrophin restoration for the cardiomyocytes to clinically relevant levels has been limited [16][17][18][19][20][21][22][23]25].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the molecular mechanisms behind MDs are partially known, this class of diseases is one of the most difficult to treat. Indeed, although several clinical trials have been carried on, MDs are still orphan diseases 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the interest in the potential of gene editing has increased, since new therapeutic strategies such as inserting dystrophin functional genes through an adenovirus,21 repairing the affected gene using the CRISPR/Cas9 technique22 or transplanting muscle stem cells to the affected muscles22 23 have proven effective.…”
Section: Introductionmentioning
confidence: 99%